ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI SEKSI INALUM CORPORATE SECRETARI (ICS) PT. INDONESIA ASAHAN INALUM - Supriadi . (JRMB (Jurnal Riset Manajemen & Bisnis), 2019)
The formulation of this research problem is whether there is an influence of work attitude towards performance. Is the influence of emotional intelligence to performance. Is there a characteristic influence of work on performance. Is there any influence of motivation to employee performance. Is there an influence of work attitude, emotional intelligence, job characteristics and performance motivation. The purpose of this research is to analyse the influence of work attitudes towards performance. To analyse the effect of emotional intelligence on performance. To analyse the influence of occupational characteristics on performance. To analyse the impact of motivation on performance. To analyse the influence of emotional intelligence work attitudes, job characteristics and performance motivation. The number of samples in this study was 38 people. The data analysis methods used are descriptive analysis and multiple linear regression analyses. Work attitude variables have a positive and significant impact on performance. The variable of emotional intelligence affects positively and significantly towards performance. Job characteristic variables have a positive and significant impact on performance. Motivation variables have a positive and significant effect on performance. Variable work attitudes, emotional intelligence, job characteristics and motivation have a positive and significant impact on performance.